2022
DOI: 10.4236/jss.2022.109022
|View full text |Cite
|
Sign up to set email alerts
|

Popular Beliefs in the Palestinian Society: An Analytic Study

Abstract: The present study addressed the popular beliefs in the Palestinian society. Popular belief practices were evaluated using an index of a 39-item scale developed by the researchers, and were administrated to 1,066 Palestinians in the West Bank, Palestine, during 2022. The sample population was selected via the stratified random selection method. Study findings revealed that almost three quarters of the participants (71.6%) experienced a moderate level of popular belief practices in their daily life. The study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Tellingly, the data indicate that the religion of the respondent had little to do with predicting level of jinn belief, suggesting that jinn belief is equally common among both Christians and Muslims. 107 However, the survey also found that women and people with less education tended to have stronger belief in jinn and related superstitions, whereas more religious people were less likely to believe in superstitious beliefs and practices associated with jinn. The opposite was true in a different survey from 2019 that found that, although only 48% of Palestinians believe in jinn possession, the belief is more prominent among religious people (55%).…”
Section: Discussionmentioning
confidence: 91%
“…Tellingly, the data indicate that the religion of the respondent had little to do with predicting level of jinn belief, suggesting that jinn belief is equally common among both Christians and Muslims. 107 However, the survey also found that women and people with less education tended to have stronger belief in jinn and related superstitions, whereas more religious people were less likely to believe in superstitious beliefs and practices associated with jinn. The opposite was true in a different survey from 2019 that found that, although only 48% of Palestinians believe in jinn possession, the belief is more prominent among religious people (55%).…”
Section: Discussionmentioning
confidence: 91%